Studi Kasus: Implementasi Health Education Teknik Buteyko Breathing Untuk Mencegah Kekambuhan Asma Dengan Media Video Pada Keluarga: Case Study: Health Education Implementation of Buteyko Breathing Technique To Prevent Asthma Recurrence With Media Video for the Family - Andan Firmansyah; Muhamad Ramdan Nujulul Furqon; Daniel Akbar Wibowo; Tita Rohita (Fakultas Keperawatan Universitas Andalas, 2023)
Asthma is a disease caused by narrowing of the airway due to inflammation or inflammation, asthma is the top 5 causes of death per year. Buteyko breathing is a deep breathing technique that is useful for strengthening the respiratory muscles. The use of videos about buteyko breathing can clarify an abstract picture about the importance of preventing asthma relapse. This case study aims to implement the Buteyko breathing technique in families with asthma patients to prevent asthma recurrence by using video media. This research uses a descriptive case study design using a nursing care approach. Methods of collecting interview data, observation, physical examination, and documentation. With the implementation of health education Buteyko breathing technique with video media which is carried out for 3x24 hours. From the results of the study, it was found that data according to the client's confession usually relapses every 1-2 weeks because of the cold weather in the early morning. Then after being given the implementation of the Buteyko breathing technique with video media when confirmed on June 19, 2022, the client claimed that he had not relapsed. The results of the case study after being given health education on the Buteyko breathing technique for the family of Mr. M understands how to prevent asthma recurrence so that the intervention is successful. Buteyko breathing intervention using video media is effective in preventing asthma relapse based on the client's subjective acknowledgment.